2015
DOI: 10.21825/vdt.v84i4.16593
|View full text |Cite
|
Sign up to set email alerts
|

Kenmerken van de voortplanting en de geassisteerde voortplanting bij de witte (Ceratotherium simum) en zwarte (Diceros bicornis) neushoorn

Abstract: Despite the worldwide increase of rhinoceros calf numbers, the growth of the population of white and black rhinoceros is slowing down mainly due to anthropogenic causes, such as poaching and habitat loss. Assisted reproduction is one of the methods of preserving the valuable genomes of these animals from being lost, and assists in breeding them in captivity to maintain the specie(s) numbers and provide an option for possible reintroduction into the wild. Since wild rhinoceros are difficult to handle and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…4E ), the embryo itself around 23 days ( Fig. 4F ) and an embryonic heartbeat at 26 days ( Radcliffe et al 1997 , Ververs et al 2015 ), mirroring the timing of these stages in the equine conceptus ( Fig. 4 ).…”
Section: Placentation and The Hormonal Control Of Early Gestationmentioning
confidence: 63%
See 1 more Smart Citation
“…4E ), the embryo itself around 23 days ( Fig. 4F ) and an embryonic heartbeat at 26 days ( Radcliffe et al 1997 , Ververs et al 2015 ), mirroring the timing of these stages in the equine conceptus ( Fig. 4 ).…”
Section: Placentation and The Hormonal Control Of Early Gestationmentioning
confidence: 63%
“…Reports on the successful application of ART in pachyderms are mostly limited to a few individuals, thus bringing the sustainability and repeatability of these techniques into question (as reviewed by Hermes et al 2007 , Ververs et al 2015 , Pennington & Durrant 2018 ). However, equine reproductive physiology and many of the ARTs in the mare have been studied for decades resulting in a wealth of knowledge and the ability to apply them routinely in clinical practice ( Hinrichs 2018 ).…”
Section: Art – Current Statementioning
confidence: 99%
“…Southern white rhinoceros as a species is conservation dependent, occurring solely in areas and on private game ranches, but it is tolerant to local human activity and can be ranched under rewilded semi-intensive and semi-extensive conditions. Under these conditions, where the density of animals is higher and regular anaesthetic procedures for management purposes and/ or translocation are likely to increase stress levels, there is no detectable difference in cow fertility [108][109]. Also, [110] found that faecal glucocorticoid metabolite (fGCM) levels do not differ between ranched and free-ranging adult rhino individuals, but routine dehorning procedures do result in short-term stress responses that dissipate after 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Trophy hunting selectively removes surplus and non-breeding adult males, whilst generating important revenue for private and state conservation (while poaching targets animals of all ages and Contribution of Private Game Ranching and CBOs in S.A. to White rhino conservation Southern white rhinoceros as a species is conservation dependent, occurring solely in protected areas and on private game ranches, but it is tolerant to local human activity and can be ranched under rewilded semi-intensive and semi-extensive conditions. Under these conditions, where the density of animals is higher and regular anaesthetic procedures for management purposes and/ or translocation are likely to increase stress levels, there is no detectable difference in cow fertility [108][109]. Also, faecal glucocorticoid metabolite (fGCM) levels do not differ between ranched and free-ranging adult rhino individuals, but routine dehorning procedures do result in short-term stress responses that dissipate after 72 hours [110].…”
Section: Performance Of Populations (Level 2 Heading)mentioning
confidence: 99%